Mo‐Compound/CNT‐Graphene Composites as Efficient Catalytic Electrodes for Quantum‐Dot‐Sensitized Solar Cells. Issue 4 (16th October 2013) - Seol, Minsu; Youn, Duck Hyun; Kim, Jae Young; Jang, Ji‐Wook; Choi, Mingi; Lee, Jae Sung; Yong, Kijung
<x xml:space="preserve">Abstract</x> Molybdenum‐based catalysts (Mo2N, Mo2C, and MoS2) supported on electrically conductive carbon nanotube–reduced graphene oxide (RGO) hybrid composites offer options for synthesizing catalytic electrodes that can replace the noble‐metal counter electrodes used in quantum‐dot‐sensitized solar cells. These electrodes display remarkable electrocatalytic activity and high stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>